Иммуногистохимическая характеристика экспрессии молекул клеточной адгезии Е-кадгерина и β-катенина в инвазивной эндометриоидной аденокарциноме матки - Туманский, В. А.; Чепец, А. В.; Туманський, Валерій Олексійович; Чепець, О. В.; Tumanskiy, V. A.; Chepets, A. V. (Запорізький державний медичний університет, 2015)
С целью определения уровней экспрессии Е-кадгерина и β-катенина клетками инвазивной эндометриоидной аденокарциномы эндометрия (ЭАЭ), а также площади иммунопозитивных клеток в центре опухоли и в зоне её инвазии в миометрий выполнено патогистологическое и иммуногистохимическое исследование операционного материала 20 больных инвазивной ЭАЭ c pT1-3 стадией распространения опухоли. В группе сравнения изучен эндометрий фазы пролиферации у 20 женщин. Экспрессию Е-кадгерина определяли с использованием моноклональных антител E-Cadherin, Clone NCH-38, а β-катенина – с применением моноклональных антител Beta-Catenin, Clone E247 ß-Catenin-1. Уровень экспрессии Е-кадгерина, β-катенина и площадь им-мунопозитивных клеток определяли фотоцифровой морфометрией в программе обработки цифровых изображений ImageJ. Установлено, что экспрессия Е-кадгерина имеет место в 95% инвазивных эндометриоидных аденокарцином эндометрия, а экспрессия β-катенина – в 100% эндометриоидных аденокарцином матки. Мембранно-цитоплазматическую экспрессию Е-кадгерина отмечали в 40% опухолей, а ядерную экспрессию β-катенина – в 10% эндометриоидных аденокарцином матки с плоскоклеточной дифференцировкой. В клетках инвазивной ЭАЭ определяется умеренный уровень экспрессии Е-кадгерина – 52,23±8,59 условных единиц оптической плотности (УЕОП), высокий уровень экспрессии β-катенина – 107,72±9,73 УЕОП. Уровни экспрессии этих молекул клеточной адгезии в инвазивной аденокарциноме матки соответственно в 2 и 5 раз ниже, чем в нормальном пролиферативном эндометрии. В инвазивной ЭАЭ Е-кадгерин-иммунопозитивные клетки занимают 20,58%±3,3% площади среза опухолевой ткани, а β-катенин-иммунопозитивные – 42,61±4,14% площади среза опухоли, что статистически достоверно меньше, чем в нормальном пролиферативном эндометрии, в котором экспрессия этих молекул определяется в 100% клеток эндометриальных желез. Различия между низким уровнем экспрессии Е-кадгерина в центре ЭАЭ и умеренным уровнем экспрессии этого маркера в зоне инвазии опухоли в миометрий, так же как и различия между высокими уровнями экспрессии β-катенина в этих зонах опухоли статистически не достоверны. Между уровнем экспрессии Е-кадгерина и β-катенина клетками инвазивной ЭАЭ существует прямая сильная корреляционная связь (коэффициент корреляции Пирсона r=+0,73). Обратная корреляционная связь умеренной силы прослеживается между уровнем экспрессии Е-кадгерина опухолевыми клетками и степенью дифференцировки опухоли (коэффициент корреляции Пирсона r=–0,67). З метою визначення рівнів експресії Е-кадгерину та β-катеніну клітинами інвазивної ендометріоїдної аденокарциноми ендометрію (ЕАЕ), а також площі імунопозитивних клітин у центрі пухлини та в зоні її інвазії в міометрій виконали патогістологічне та імуногістохімічне дослідження операційного матеріалу 20 хворих на інвазивну ЕАЕ з pT1-3 стадією поширення пухлини. У групі порівняння досліджений ендометрій фази проліферації у 20 жінок. Експресію Е-кадгерину визначали за допомогою моноклональних антитіл E-Cadherin, Clone NCH-38, а експресію β-катеніну – із застосуванням моноклональних антитіл Beta-Catenin, Clone E247 ß-Catenin-1. Рівень експресії імуногістохімічних маркерів пухлинними клітинами та площу імунопозитивних пухлинних клітин визначали за допомогою фотоцифрової морфометрії у програмі обробки цифрових зображень ImageJ. Встановили, що експресія Е-кадгерину наявна в 95% інвазивних ендометріоїдних аденокарцином ендометрію, а експресія β-катеніну – у 100% ендометріоїдних аденокарцином матки. Мембранно-цитоплазматичну експресію Е-кадгерину виявляли в 40% пухлин, а ядерну експресію β-катеніну – в 10% ендометріоїдних аденокарцином матки із плоскоклітинним диференціюванням. У клітинах інвазивної ЕАЕ визначається помірний рівень експресії Е-кадгерину – 52,23±8,59 умовних одиниць оптичної щільності (УООЩ) високий рівень експресії β-катеніну – 107,72±9,73 УООЩ. Рівні експресії цих молекул клітинної адгезії в інвазивній аденокарциномі матки у 2 та 5 разів нижчі відповідно, ніж у нормальному проліферативному ендометрії. В інвазивній ЕАЕ Е-кадгерин-імунопозитивні клітини займають 20,58%±3,3% площі зрізу пухлинної тканини, а β-катенін-імунопозитивні – 42,61±4,14% площі зрізу пухлини, що статистично вірогідно менше, ніж у нормальному проліферативному ендометрії, в якому експресія цих молекул визначалася в 100% клітин ендометріальних залоз. Відмінності між низьким рівнем Е-кадгерину в центрі ЕАЕ та помірним рівнем експресії цього маркера в зоні інвазії пухлини в міометрій, також як і відмінності між високими рівнями експресії β-катеніну в цих зонах пухлини статистично невірогідні. Між рівнем експресії Е-кадгерину та β-катеніну клітинами інвазивної ЕАЕ наявний прямий сильний кореляційний зв’язок (коефіцієнт кореляції Пірсона r=+0,73). Зворотний кореляційний зв’язок помірної сили простежується між рівнем експресії Е-кадгерину пухлинними клітинами та ступенем диференціювання пухлини (коефіцієнт кореляціях Пірсона r=–0,67). Aim. In order to determine E-cadherin and β-catenin expression levels in the invasive endometrioid endometrial carcinoma (EEC) cells and areas of the immunopositive cells in the center of the tumor and in the area of tumor invasion into the myometrium a pathohis tological and immunohistochemical study of histological specimens of operative material of 20 patients with pT1-3 stage of tumor was performed. In the comparison group the proliferative-phase endometrium of 20 women was studied. E-cadherin expression by tumor cells was determined using monoclonal antibodies E-Cadherin, Clone NCH-38 and expression of β-catenin – in the use of monoclonal antibodies Beta-Catenin, Clone E247 ß-Catenin-1. Methods and results. The expression levels of immunohistochemical markers in tumor cells and tumor cells immunopositive areas were determined by photo digital morphometry in digital image processing program Image J. It was found that E-cadherin expression occurs in 95% of invasive endometrioid endometrial carcinomas and β-catenin expression takes place in 100% of EEC. Membranecytoplasmic expression of E-cadherin was observed in 40% of tumors, and 10% of endometrioid adenocarcinomas of the uterus with squamous differentiation showed nuclear β-catenin expression. There was a moderate expression level of E-cadherin (52,23±8,59 CUOD) and high expression level of β-catenin (107,72±9,73 CUOD) in the cells of invasive EEC. These levels are 2 and 5 times lower than in normal proliferative endometrium: the expression level of E-cadherin is 116,51±8,5 CUOD and β-catenin expression level is 159,7815±3,57 CUOD. E-cadherin immunopositive cells make up 20,58%±3,3% of area of invasive EEC tissue section and β-cateninimmunopositive cells make up 42,61±4,14% of area of tumor tissue section. That is statistically signifi cantly less than in normal proliferative endometrium, which has 100% β-catenin and E-Cadherin immunopositive cells of endometrial glands. The differences between low E-cadherin expression level in the center of EEC and moderate expression level of this marker in the region of tumor myometrial invasion, as well as differences between high expression levels of β-catenin in these areas of the tumor were not statistically signifi cant. There is a direct strong correlation between the E-cadherin and β-catenin expression levels in the cells of EEC (Pearson correlation coeffi cient r = +0,73). The inverse moderate correlation is revealed between the expression level of E-cadherin in tumor cells and the degree of tumor differentiation (Pearson correlation coeffi cient r = –0,67).
Імуногістохімічна характеристика експресії молекул клітинної адгезії Е-кадгерину та β-катеніну в інвазивній ендометріоїдній аденокарциномі матки
Immunohistochemical characterization of the expression of cell adhesion molecules E-cadherin and β-catenin in the invasive endometrioid endometrial carcinoma
Keywords: карцинома эндометрия; молекулы клеточной адгезии; Е-кадгерин; β-катенин; карцинома ендометрію; молекули клітинної адгезії; E-кадгерин; β-катенін; Endometrial Carcinoma; Cell Adhesion Molecules; E-Cadherin; beta-Catenin